A Study on the Trade and Investment Policies of Developing Countries: The Case of the Philippines - Erlinda M. Medalla; Myrna S. Austria (Philippine Institute for Development Studies (PIDS), 1996)
Recognition of the adverse effects of protectionist policies has lead to the Philippine government to undertake major trade reforms in the 1980s and 1990s having efficiency and competitiveness as objectives. This study analyzes the impact of Philippine trade and investment policies on economic growth and on the performance of the manufacturing industries. This also analyzes the trends of the Philippine-Japan economic relations focusing on trade, investments and development assistance and provides possible directions in the role of Japan in the future Philippine development.
Keywords: 330